Transformation of Conventional Banking to Digital Banking: Regulation and Risk Management - Ma'rifah, Aula Nurul; Pranata, Eka Octavian; Nabilah, Deva; Arini, Erni Zulfa (Universitas Islam Negeri Raden Intan, 2024)
This research discusses the transformation of conventional banks to digital banking by emphasizing the importance of regulation and risk management. The method used is literature review, collecting and reviewing references related to OJK regulations governing digital banking services and risk management related to digital banks. The results show that strong regulations are needed to protect consumers and ensure the stability of the digital banking system. In addition, banks must implement adequate risk management to address threats such as cybersecurity, data protection, and operational risks. Good risk management allows banks to mitigate the negative impacts that may arise during the digitalization process. This research emphasizes the importance of regulation and comprehensive risk management in maintaining sustainability and customer trust in digital banking.